"I am in other people's hands as regards my health" A sociological critique of health care encounters of people with cirrhosis. A secondary analysis. (March 2023) - Davis, Sarah; Higgs, Paul; Jones, Louise; Greenslade, Lynda; Wilson, Jo; Low, Joseph TS; ,
Objectives: People with cirrhosis are encouraged to participate in shared decision-making with their doctors, but studies suggest that doctors limit the amount of information that is shared. In this study we explore the presence of medical power in clinical encounters in 2015 from a patient perspective and highlight its effects on healthcare interactions. Methods: Qualitative semi-structured interviews were conducted with ten people with cirrhosis attending a tertiary liver transplant centre in southern England. We explored their understanding of their disease and prognosis, and their participation in decision-making. Using the lens of medical power as a framework, we analysed findings into thematic sentences to summarise key ideas whilst preserving the complexity of identified concepts. Results: Three key concepts explained patient perspectives of their communication with doctors: (1) portraying a positive image to doctors, (2) avoiding confrontation with doctors, (3) feeling powerless in the face of doctors' medical knowledge. These concepts show deeper dynamic issues of power during healthcare encounters, illustrated by participants' reluctance to voice their concerns and express themselves, challenge decisions, or seek information. Conclusion: People with cirrhosis struggle to articulate their concerns or challenge decisions on their care and treatment and may worry about potential consequences. Our findings demonstrate the continuing persistence of issues of power at play in contemporary health care.